2020
DOI: 10.1007/s12274-020-3028-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic-immune therapy with a multi-purpose black phosphorus-based nanoparticle

Abstract: Effective therapeutic strategies to precisely eradicate primary tumors with minimal side effects on normal tissue, inhibit metastases, and prevent tumor relapses, are the ultimate goals in the battle against cancer. We report a novel therapeutic strategy that combines adjuvant black phosphorus nanoparticle-based photoacoustic (PA) therapy with checkpoint-blockade immunotherapy. With the mitochondria targeting nanoparticle, PA therapy can achieve localized mechanical damage of mitochondria via PA cavitation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Therefore, it is critical to develop localized and precise immunotherapeutic strategies against cancer. Multifunctional nanotheranostic systems can proactively accumulate at target sites and deliver drugs in a controlled manner, thereby achieving high therapeutic efficacy with minimal side effects. In particular, photoacoustic (PA) imaging-guided precision therapy has attracted extensive attention due to its excellent tissue penetration and high temporal and spatial resolution. For example, nanocarriers loaded with contrast agents can achieve precise optical image-guided photocontrolled drug release, which significantly reduces the off-target and side effects of drugs. ,, However, this approach has not been attempted in ICB therapy due to the thermal instability of PD1/PDL1 antibodies. Recently, aptamers of immune checkpoints have been screened, allowing PA imaging-guided photothermal immunotherapy. However, traditional nanocarriers have poor histocompatibility and stability and may bind to serum proteins and immune cell components in the blood, resulting in their elimination by the immune system.…”
mentioning
confidence: 99%
“…Therefore, it is critical to develop localized and precise immunotherapeutic strategies against cancer. Multifunctional nanotheranostic systems can proactively accumulate at target sites and deliver drugs in a controlled manner, thereby achieving high therapeutic efficacy with minimal side effects. In particular, photoacoustic (PA) imaging-guided precision therapy has attracted extensive attention due to its excellent tissue penetration and high temporal and spatial resolution. For example, nanocarriers loaded with contrast agents can achieve precise optical image-guided photocontrolled drug release, which significantly reduces the off-target and side effects of drugs. ,, However, this approach has not been attempted in ICB therapy due to the thermal instability of PD1/PDL1 antibodies. Recently, aptamers of immune checkpoints have been screened, allowing PA imaging-guided photothermal immunotherapy. However, traditional nanocarriers have poor histocompatibility and stability and may bind to serum proteins and immune cell components in the blood, resulting in their elimination by the immune system.…”
mentioning
confidence: 99%
“…The contribution of the PAI system combined treatment to treat cancer goes far beyond the strategies mentioned above. In recent years, scientists have aroused great interest in PA system-guided immunotherapy due to the rise of tumor immunotherapy. , By labeling specific enzymes or biomarkers with PA contrast agents, the autoimmune function of tumor sites can be activated to promote the body’s immune cells to attack tumor cells. Up to now, the process of immunotherapy at a single cell level can be real-time monitored via PA labeling of bioactive substances, which were widely reported to obtain satisfactory treatment.…”
Section: Principles Of Pai and Applications For Cancer Theragnosticsmentioning
confidence: 99%
“…Different from PDT with limited ROS yield and PTT with overheat, BP-based PAT shockwave generation can achieve precise attack on the tumor site. In Zeng's study, they prepared multifunctional BP nanoparticles targeting mitochondria, and shockwave generated by the nanoparticles under the action of PAT produced the precise destruction to mitochondria and induced effective ICD effects [ 85 ]. Therefore, it can be concluded that PAT may bring a new round of innovation in precision cancer treatment.…”
Section: Bp-based Therapeutic Strategiesmentioning
confidence: 99%
“…BP-based PIT combined with CTLA4 inhibitors could significantly inhibit Tregs-mediated immunosuppression with an increase of the ratios of CD8+ CTLs/Tregs and CD4+ Teff/Tregs. Moreover, combination therapy also elicited a memory CTL immune response that prevented recurrence and metastasis of tumors [ 85 ].…”
Section: The Potential Of Bp In Immunotherapymentioning
confidence: 99%